Defect Engineering of Photocatalysts for Solar Energy Conversion. Issue 4 (3rd April 2020) - Ran, Lei; Hou, Jungang; Cao, Shuyan; Li, Zhuwei; Zhang, Yanting; Wu, Yunzhen; Zhang, Bo; Zhai, Panlong; Sun, Licheng
Abstract : Defect Engineering Defect engineering has been proven a promising solution involving photocatalysts for converting solar energy to chemical energy. In article number 1900487, Jungang Hou, Licheng Sun, and co‐workers provide an in‐depth understanding of the tunable defects, synthesized strategies, and characterization techniques of the controllable defects and highlight the roles of defect engineering upon solar energy application in this rapidly developing field.